THE IDEAL ISLAMIC STATE IN SHAYKH ALIKINLA'S MUSTAQBAL ILORIN AL-ZAHIR (1990)
This thesis consists of nine chapters. The first is on the biography of the Shaykh while the second highlights the features of an ideal Islamic State. The subsequent chapters critically examine the views expressed by the Shaykh after editing the Arabic text and translating it. Topics discussed in the chapters respectively are patriotism, agriculture and commerce, education, family living, and health and social welfare services. Shaykh Abd al-Salam Yusuf A1 ikinla was an erudite scholar and a gifted writer. He was also a charismatic leader who commanded the respect of all and sundry, especially the -Western-educated Muslims who constituted the majority of members of Hizbulabah-al-Shalib, founded by him in 1952. His efforts to enhance the status of Islam and that of its adherents attracted him to the political activities of the 1940s and 1950s although he never contested for any public post. It is not impossible that Mustaqbal Ilorin al-Zahir, now under study, is as a result of his exposure to politics. Under patriotism, issues affecting security of the nation and commitment of the citizens to uphold its territorial integrity are discussed. Care of the land and encouragement of farmers financially and morally are treated under agriculture. The Shaykh talks about traders, foreign entrepreneurs and artisans under commerce. Much emphasis is laid on proper upbringing of girls, their freedom to study any course and compulsory education of every child under education. On family living, the Shaykh raises issues such as the establishment of marriage registry, size of the family, mothers' responsibilities to their children and the influence of the former on the latter. Topics treated under health services include qualities of animals to be slaughtered, environmental sanitation, traditional and modem physicians and training of doctors and para-medical staff locally and abroad. His discussions on social welfare services cover the settlement of the destitute such as beggars, lunatics and lepers. It is pertinent to mention here that the Shaykh's belief that Islam is not only a religion but a complete way of life underlies his submissions on the topics mentioned above. His intention seems to be the spiritual and material transformation of the nation into a better society.